2011
DOI: 10.1002/humu.21604
|View full text |Cite
|
Sign up to set email alerts
|

Variants in activators and downstream targets of ATM, radiation exposure, and contralateral breast cancer risk in the WECARE study

Abstract: Ionizing radiation is a breast carcinogen that induces DNA double strand breaks (DSBs), and variation in genes involved in the DNA DSB response has been implicated in radiation-induced breast cancer. The Women’s Environmental, Cancer and Radiation Epidemiology (WECARE) Study is a population-based study of cases with contralateral breast cancer (CBC) and matched controls with unilateral breast cancer. The location-specific radiation dose received to the contralateral breast was estimated from radiotherapy recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…Recruitment, eligibility criteria, data and biospecimen collection, and genotype methods have been described (2, 4). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recruitment, eligibility criteria, data and biospecimen collection, and genotype methods have been described (2, 4). …”
Section: Methodsmentioning
confidence: 99%
“…Twelve candidate genes were selected based on biological plausibility and known involvement with adipose tissue metabolism and obesity ( LEP , LEPR , ADIPOQ , ADIPOR1 , ADIPOR2 , HIF1A , PLAU , PLAUR , SERPINE1, IGF2BP1 ) (3) or a functional relationship with both obesity and DNA repair ( IRS2 , FOXO1 ) (8). SNPs identified from GWAS were genotyped directly, whereas SNPs in candidate genes were selected using a tagSNP approach, supplemented with potentially functionally relevant SNPs from dbSNP (4). A total of 194 SNPs in 20 genes was genotyped.…”
Section: Methodsmentioning
confidence: 99%
“…An Chinese study reported a variant allele of MDC1 exhibited a significant association with EBV seropositivity [28]. A Caucasian study reported no variant of MDC1 was associated with breast cancer risk as well as DNA-damaging effects of radiation therapy [47]. However, the above studies were all lack of study power because of their limited sample sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Brooks et al (2012) examined 152 SNPs from six genes (CHEK2, MRE11A, MDC1, NBN, RAD50, and TP53BP1) were genotyped in the WECARE cohort to see if any of them conferred a higher risk for CBC. The MRN complex or MRE11-RAD50-NSB1 complex is part of the BRCA1 associated genome surveillance complex.…”
Section: Rad50mentioning
confidence: 99%